(untitled) (Indian Journal of Arid Horticulture, 2018)
Underutilized crops have the immense potential to provide social, nutritional and environmental benefits to global community at large and local poor inhabitants in particular. Many underutilized species in arid zone are known for their edible fruits or as vegetables viz. kair (Capparis decidua), lasora (Cordia myxa), jhar ber (Ziziphus nummularia), pilu (Salvadora oleoides), khejri (Prosopis cineraria), phalsa (Grewia subinaequalis), bael (Aegle marmelos), karonda (Carissa carandas), fig (Ficus carica) and tahiti lime (Citrus latifolia) etc. However, intensive work on germplasm collection, evaluation and improvement was done on lasora, karonda and khejri which resulted in identification of some high yielding genotypes in these crops. In case of lasora, 13 germplasm accessions were collected and evaluated from which four high yielding accessions viz. CAZRI-G2025, CAZRI-G2021, CAZRI-G2012 and CAZRI-G2011 were found promising. Among the 8 accessions collected and evaluated in karonda, the accessions, CZK-2011, CZK-2022 and CZK-2031 have shown high yield potential. Seven germplasm collections of budded khejri including the variety Thar Shobha were evaluated for pod quality and yield. The highest pod yield was recorded in CAZRI-Kh-1(13.2kg/plant) followed by CAZRI-Kh-2(11.6 kg/plant) in seventh year.